2021
DOI: 10.3389/fendo.2021.722055
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Metagenomics and Metabolomics to Reveal the Effects of Policosanol on Modulating the Gut Microbiota and Lipid Metabolism in Hyperlipidemic C57BL/6 Mice

Abstract: The aim of the study was to investigate the regulatory effects of policosanol on hyperlipidemia, gut microbiota and metabolic status in a C57BL/6 mouse model. A total of 35 C57BL/6 mice were assigned to 3 groups, chow (n=12), high fat diet (HFD, n=12) and HFD+policosanol (n=11), then treated for 18 weeks. Policosanol supplementation significantly reduced serum triglycerides and total cholesterol, as well as the weight of brown adipose tissue (BAT) (p<0.05), without affecting body weight in HFD-fed mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…A Q-Exactive-MS spectrometer was employed to obtain MS/MS spectra of metabolites with the monitoring of acquisition software (Xcalibur 4.1, Thermo-Fisher), and the parameters of ESI conditions were according to a previous report 18 with minor modifications.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…A Q-Exactive-MS spectrometer was employed to obtain MS/MS spectra of metabolites with the monitoring of acquisition software (Xcalibur 4.1, Thermo-Fisher), and the parameters of ESI conditions were according to a previous report 18 with minor modifications.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…A large number of studies have indicated that dietary fiber intake is negatively correlated with chronic metabolic disorders and promotes health (Makki et al, 2018;Zhao and Zhang, 2018). Previous studies have revealed that obesity is often characterized by an increase in the proportion of Firmicutes and a decrease in Bacteroides (Ye et al, 2021;Zhai et al, 2021). Notably, dietary fiber can regulate the gut microbiota structure and contribute to fermentation products, in particular, short-chain fatty acids (SCFAs), which are considered important signaling molecules and beneficial for human health (Koh et al, 2016;Makki et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Policosanol reduced LDL-cholesterol and triglyceride levels, increased HDL-cholesterol levels, and reduced systolic blood pressure in a double-blind, placebo-controlled, and parallel clinical trial with women with prehypertension [ 285 ]. In comparison to a high-fat diet, healthy C57BL/6 mice that were fed a high-fat diet with 0.5% policosanol for 18 weeks developed a better lipid profile, a reduction in brown and white inguinal adipose tissue, a distinctive microbiota profile, and enhanced lipolysis and thermogenesis [ 292 ], while, in a similar study, 60 mg/kg of either octacosanol or policosanol protected against visceral fat hyperplasia and liver steatosis [ 293 ]. Beneficial effects of phytosterols on LDL-cholesterol are well established, with a mean reduction of 8–10% [ 294 ] and significant reductions in ApoCII and ApoE [ 295 ].…”
Section: Resultsmentioning
confidence: 99%